2021
DOI: 10.3390/ijms222212579
|View full text |Cite
|
Sign up to set email alerts
|

Isoprocurcumenol Supports Keratinocyte Growth and Survival through Epidermal Growth Factor Receptor Activation

Abstract: Although proliferation of keratinocytes, a major type of skin cells, is a key factor in maintaining the function of skin, their ability to proliferate tends to diminish with age. To solve such a problem, researchers in medical and skin cosmetic fields have tried to utilize epidermal growth factor (EGF), but achieved limited success. Therefore, a small natural compound that can mimic the activity of EGF is highly desired in both medical and cosmetic fields. Here, using the modified biosensor system, we observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Comparing the results of this study with other previous studies [[ [16] , [17] , [18] , [19] , [24] , [25] , [76] ]indicated that this structure could probably contribute significantly in wound healing with the synergistic effect of the hydrogel and peptide through improving different phases of healing ( Table 2 ).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Comparing the results of this study with other previous studies [[ [16] , [17] , [18] , [19] , [24] , [25] , [76] ]indicated that this structure could probably contribute significantly in wound healing with the synergistic effect of the hydrogel and peptide through improving different phases of healing ( Table 2 ).…”
Section: Resultssupporting
confidence: 81%
“…Therefore, a small molecule imitating EGF's effects by influencing the certain cell signaling pathways could be effective in wound repair [ 16 ]. Based on this, a variety of wound-healing peptides have been unveiled during recent years, showing significant potential for wounds management.…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative data are shown as means ± SEM, which were statistically analyzed by unpaired Student's t tests in the case of the two groups. One-way or two-way analysis of variance (ANOVA) was conducted by using PRISM software (GraphPad Software), which was previously described [25][26][27][28]. A result of p < 0.05 was considered to represent significance.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 54 germacrane sesquiterpenoids have been isolated from Curcumae Rhizoma (Figure 2, Table 2). These natural products frequently engage in the formation of a five-membered ring at C-8 and C-12, yielding diverse structural moieties, such as furan rings (139)(140)(141)(142)(143)(144)(145), lactone rings (146)(147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158), and lactam rings (161-168). This type of compound is prone to oxidation, which can produce aldehydes, ketones, esters, or oxygen bridges.…”
Section: Germacrane-type Sesquiterpenoids Of Curcumae Rhizomamentioning
confidence: 99%
“…These compounds actively diminish free radical concentrations within the organism, alleviate oxidative harm, and consequently hold promise in the prevention and treatment of associated diseases [80]. In the context of skin regeneration, it has been discovered that alismoxide (3), isozedoarondiol (20), isoprocurcumenol (43), germacrone (116), and 13-hydroxygermacrone (124) can activate the epidermal growth factor receptor, thereby promoting skin regeneration [142][143][144]. In relation to other activities, procurcumenol (29), germacrone (116), and dehydrocurdione (121) also exhibit neuroprotective effects [143]; curcumanolide A (241) has a relaxant effect on uterine smooth muscle tissue [15]; curdione (117) attenuates sepsis-induced lung injury [145]; curcumenol (61) reduces disc inflammation and improves disc catabolism [146]; zederone (143) has the potential to be a drug for the treatment of dementia [147]; and curcumenone (258) can exert a protective effect against intoxication [148].…”
Section: Other Biological Activitiesmentioning
confidence: 99%